PARALLEL MINING OF LARGE MAXIMAL BICLIQUES USING ORDER PRESERVING GENERATORS - Nataraj, R. V.; Selvan, S. (International Journal of Computing, 2014)
In this paper, we propose a parallel algorithm for mining large maximal bicliques from graph datasets. We propose POP-MBC (Parallel Order Preserving Maximal BiClique mining algorithm), a fast and memory efficient parallel algorithm, which enumerates all the maximal bicliques independently and concurrently across several processors without any synchronization between the processors. The POP-MBC algorithm is highly memory efficient since it does not store the previously computed patterns in the main memory and requires only the dataset to be stored in the memory. To enhance the load sharing among different nodes, POP-MBC uses a round robin strategy which enables to achieve load balancing as high as 90%. We have also incorporated bit-vectors and numerous optimization techniques exploiting the symmetric property of the graph dataset to reduce the memory consumption and overall running time of the algorithm. Our comp rehensive experimental analyses involving publicly available datasets show that our algorithm distributes the load among the different processors equally and takes less memory, less running time than other maximal biclique mining algorithms.